PENGARUH LEARNING ORGANIZATION DAN SUPERVISI MANAJERIAL TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KABUPATEN ACEH BARAT - Taruna, Wilis; Marwan, Marwan; Rizki, Sari (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
Research objectives 1) to determine the influence of Learning Organization on teacher performance at State Elementary Schools in West Aceh Regency; 2) to determine the effect of the principal's managerial supervision on teacher performance at state elementary schools in West Aceh Regency. This research was carried out at the Regional Office Technical Implementation Unit 1 in cluster 1, Meureubo District, West Aeh Regency using quantitative methods. The research population was 212 people, the sample was 68 people, the sample was determined using the Taro Yamane formula. using an error acceptance of 10%. Research findings resulting from hypothesis testing using determination analysis (R), t-test, and simple regression can be concluded from the results of analysis tests using correlation test analysis, simple linear regression test, partial test (t-test) and determinant coefficient test (r), it can be concluded that teacher performance influences the learning organization. The results of the correlation coefficient are 0.304 with a significant value of 0.012, there is a positive relationship between learning organization and teacher performance. Meanwhile, the correlation coefficient value (rcount) is compared with (rtable) with an alpha value of 0.012 (5%). By calculating the results of the Pearson product moment correlation test, the rcount value is 0.304, while the rtable is 0.265. Therefore, it can be concluded that the value of rcount > rtable (0.304 > 0.265), this is in accordance with the rules of hypothesis testing with a significant level of alpha value <0.05, so the first hypothesis is accepted, meaning that there is an influence of learning organization on teacher performance. The results of the r table validity test can be calculated in the statistical r-table with a two-way test based on the formula df = n-2 so 68-2 = 66 with an error level of 0.5%, variable X at p1, p5, p6, p7, p9 and the variable Y p10 has a different value from the other questions but it is still said to be valid. So the rtable results in the validity test show a dominant value of 0.322. So it can be concluded that the person coreelation value (rcount) is greater than the value (rtable), so that the entire number of question items in the results of this research are declared valid. The influence of the principal's managerial supervision on teacher performance is based on the results of the reliability test of the two variables, namely variable X teacher performance obtained a Cronbach apha value of 0.701 and variable Y teacher performance obtained a Cronbach apha value of 0.747. Thus the second research hypothesis is accepted.